Anatomical Relationship of Lingual Nerve to the Region of Mandibular Third Molar - Marcelo Breno Meneses Mendes (eJournal of Oral Maxillofacial Research, 2014)
Objectives: This study evaluated the relationship of the lingual nerve with the adjacent anatomical structures of the mandibular third molar region, influencing the dentist to be aware of the variability of these relationships.